La bioseguridad y su impacto en la prevención de enfermedades nosocomiales registrados en el hospital Martin Icaza de la ciudad de Babahoyo en el periodo del primer semestre del 2012 - Guapulema Martínez, Nancy Magaly (2012)
Diseases Nosocomial or are a priority health problem in the country because, as is known, nosocomial infections are associated with biosecurity procedures in patient care clinical decision closely related and that the most common hospital infections are endemic , no epidemic, with limited importance of the hospital environment in their generation. The Ministry of Public Health of the Republic of Ecuador, pursuant to its steering, has developed a biosafety manual control of nosocomial infections to develop fully in the service delivery network of the health system, since infections nosocomial are an important cause of morbidity and mortality……